Pengaruh NPM, ROA, ROE Terhadap Pertumbuhan Laba Dengan BOPO Sebagai Moderasi - Siti Meisaroh; Tatas Ridho Nugroho; Nurdiana Fitri Isnaini; Imam Baidlowi (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The aim of this study is to find out the impact of NPM, ROA, and ROE on BOPO-moderated profit growth in food and beverage sub-sector manufacturing companies in the period 2017–2022. This type of research is called quantitative descriptive research. The population used 26 food and beverage companies. The samples used in this study were from 14 companies, for a total of 84 samples obtained using purposive sampling techniques. Data analysis techniques use descriptive statistics, classical assumption tests that include normality tests, multicolinerity tests, heteroskedasticity tests, and autocorrelation tests, double linear regression analysis, moderated regression analyses, hypothetical tests (t tests), and determination coefficients with the help of SPSS program 26. The secondary data used is the financial report obtained from the Indonesian Stock Exchange. The results of the research show that NPM has no influence on profit growth, while ROA and ROE influence profit growth, and BOPOs are not able to moderate the relationship between NPM to profit growth. BOPOs are not capable of moderating the relationship between ROA to profit growth, BOPOs are not capable of moderating the relationship between ROE to profit growth Keywords: NPM, ROA, ROE, BOPO and Profit Growth